A ressignificação do decálogo na perícope de Mateus 5.17-48. - Araújo, Maelite Costa de (2017)
The present research will contemplate the dynamics of intertextuality, involving pericopes of Exodus and Deuteronomy and the Gospel according to Matthew, all referring to the Decalogue. Interpreting the Scriptures using their own texts, was already a practice of the Jewish tradition, and can be found in the biblical tradition. Nowadays, theology lives in a phase in which scholars turn to this type of literary technique. The title of this research "The re-signification of the Decalogue in the pericope of Matthew 5.17-48", will make possible the use of this technique. In order to understand how Jesus made this re-signification, the following subjects will be analyzed: the community and the gospel according to Matthew; the pericope of Matthew 5: 17-48; the way Jesus re-signified the Decalogue through the antitheses existing in this pericope. The research will be of bibliographical characteristics and will focus on the investigation on the following question: can the pericope of Mt 5: 17-48 be considered a re-signification of the Decalogue? If the answer is positive, what is this resignification like? Biblical dictionaries, commentaries on the books of Exodus, Deuteronomy and the Gospel according to Matthew, commentaries on the Old and New Testaments, encyclopedias and articles of the internet, among others, will be consulted for this analysis.